Management of ovarian cysts during pregnancy. Issue 9 (September 2022) - Bhagat, Nanak; Gajjar, Ketankumar
Abstract: Ovarian cysts are common in pregnancy, more so with the increase in routine antenatal use of ultrasonography. The majority of ovarian cysts in pregnancy are benign and resolve spontaneously. It is rare to diagnose malignant ovarian tumours during pregnancy. Imaging with ultrasonography is the first line investigation of choice and the use of International Ovarian Tumor Analysis (IOTA) group rules of ultrasonographic appearances of ovarian lesions can help identify benign and malignant lesions more accurately. MRI is also safe to use in pregnancy to better delineate ovarian lesions. Simple cysts <6 cm can be safely managed conservatively, with surgery reserved for larger, symptomatic cysts or those suspicious of malignancy. Ovarian cysts can be managed laparoscopically between 14 and 16 weeks gestation but require advanced laparoscopic skills. Image guided aspiration of benign ovarian cysts remains an option but is associated with high recurrence rates and risk of spillage, a disadvantageous outcome in cases subsequently shown to be malignant.